Study of malondialdehyde as an oxidative stress marker in schizophrenia - Dahake, Hemant S.; Warade, Jayesh; Kansara, Gaurav S.; Pawade, Yogesh; Ghangle, Suresh (International Journal of Research in Medical Sciences, 2016)
Background: Schizophrenia is characterized by distortions in thinking, perception, emotions, language, sense of self and behaviour. It has been demonstrated that free radical-mediated damage has an important role in the pathophysiology of schizophrenia. The present study was undertaken to study malondialdehyde as an oxidative stress marker in first episode and chronic schizophrenic patients. Methods: 50 patients of first episode schizophrenia and 50 patients of chronic schizophrenia were included in the study. 50 numbers of age and sex matched healthy and apparently normal controls were also selected for study. Blood samples were drawn and analysed for malondialdehyde (MDA) from all participants. Results: The study shows significant increase in plasma malondialdehyde (MDA) levels in both first episode schizophrenics and chronic schizophrenic patients as compared to controls. When we compared levels of these parameters in first episode schizophrenics and chronic schizophrenics, we did not find significant difference. Conclusions: Findings in our study is suggesting that increase in the levels of plasma malondialdehyde (MDA) occurs due to increased lipid peroxidation in schizophrenics.